2021
DOI: 10.1177/0271678x211020863
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cerebral hemodynamic dysregulation in middle-aged APOE ε4 carriers: The PREVENT-Dementia study

Abstract: Accumulating evidence suggests vascular dysregulation in preclinical Alzheimer’s disease. In this study, cerebral hemodynamics and their coupling with cognition in middle-aged apolipoprotein ε4 carriers (APOEε4+) were investigated. Longitudinal 3 T T1-weighted and arterial spin labelling MRI data from 158 participants (40–59 years old) in the PREVENT-Dementia study were analysed (125 two-year follow-up). Cognition was evaluated using the COGNITO battery. Cerebral blood flow (CBF) and cerebrovascular resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
4
26
0
Order By: Relevance
“…This result was consistent with previous studies from the same cohort that have reported significant negative associations of CAIDE scores with visuospatial functions and navigational abilities (Ritchie et al, 2018;Ritchie et al, 2017). We did not observe a longitudinal effect, similarly to other studies of this cohort (Dounavi et al, 2021;Low et al, 2021), possibly due to the relatively young age range of the sample and the short follow-up window (Ritchie et al, 2018;Ritchie et al, 2017). We caution that the interpretability of the effect of risk on each individual function is limited by their composite assessment in this study and requires individuation in future studies with a longer longitudinal follow-up window.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with previous studies from the same cohort that have reported significant negative associations of CAIDE scores with visuospatial functions and navigational abilities (Ritchie et al, 2018;Ritchie et al, 2017). We did not observe a longitudinal effect, similarly to other studies of this cohort (Dounavi et al, 2021;Low et al, 2021), possibly due to the relatively young age range of the sample and the short follow-up window (Ritchie et al, 2018;Ritchie et al, 2017). We caution that the interpretability of the effect of risk on each individual function is limited by their composite assessment in this study and requires individuation in future studies with a longer longitudinal follow-up window.…”
Section: Discussionsupporting
confidence: 93%
“…The use of composite cognitive domains that capture slightly different functions in the two assessment points [24] prevents investigation of the impact of lifestyle on cognitive changes over time in this study. Nevertheless, previous studies from this cohort have shown only subtle changes over the two year period [56-57], possibly due to the relatively young age range of the sample and the short follow up window [23, 39]. Therefore, future studies that follow this cohort over a longer period and test hypotheses informed by the previous study waves are needed to determine the longitudinal impact of lifestyle activities in cognitively healthy middle-aged individuals at risk for late life AD.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to Aβ deposition, recent evidence from neuroimaging cohort studies and animal models strongly suggests other underlying pathophysiological processes of AD, particularly neurovascular dysregulation ( Iturria-Medina et al, 2016 ; Dounavi et al, 2021 ). Vascular dysfunction result in reduced clearance of Aβ by periarteriolar and impaired Aβ transporters across the blood-brain barrier, which can increase Aβ deposition.…”
Section: Introductionmentioning
confidence: 99%